2010
DOI: 10.1007/s00066-010-2096-3
|View full text |Cite
|
Sign up to set email alerts
|

Pineal Parenchymal Tumors

Abstract: This study indicates that stereotactic (125)I-IRS for the management of PPTs is quite efficient and safe. Due to the low rate of side effects, IRS may develop into an attractive alternative to microsurgery in de novo diagnosed pineocytomas. In malignant PPTs, IRS may be routinely applied in a multimodality treatment schedule supplementary to conventional irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…However, we must scrutinize whether our strict inclusion criteria might have contributed to the obtained favorable results. However, previous reports using IBT for the treatment of brain tumors have also shown its efficacy [10,[13][14][15][16]. Stereotactic interstitial brachytherapy for the treatment of oligodendroglial brain tumors [6,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we must scrutinize whether our strict inclusion criteria might have contributed to the obtained favorable results. However, previous reports using IBT for the treatment of brain tumors have also shown its efficacy [10,[13][14][15][16]. Stereotactic interstitial brachytherapy for the treatment of oligodendroglial brain tumors [6,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 67 patients underwent IBT for the treatment of intracranial oligodendroglial tumors between January 1991 and December 2010 in our department. In addition, patients with an OG WHO III without receiving external fractionated irradiation prior to IBT obtained an adjuvant external fractionated irradiation boost with a median total dose of 25.2 Gy (range 20-36 Gy) according to our schedule for gliomas [9,10]. Four patients were lost to follow-up; hence, 63 patients (male/female ratio 30/33; median age 43.3 years, range 20.8-63.4 years) were evaluated in this study.…”
Section: Patientsmentioning
confidence: 99%
“…Complete remission rate was 72% and partial remission rate 28%. Maarouf et al concluded that iodine-125 seeds are efficient and safe and an attractive alternative to microsurgery [165]. All in all, iodine-125 brachytherapy treatment with a low dose rate seems to be an attractive, minimally invasive treatment option of these rare tumour entities of the pineal region.…”
Section: Reviewmentioning
confidence: 99%
“…Of the 2701 articles retrieved in the search, 44 studies with IPD on 298 patients with pineoblastoma were included in the systematic review ( Table 1 ) [ 5 , 6 , 8 , 9 , 10 , 11 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Figure 1 presents the PRISMA flowchart for this systematic review [ 18 ].…”
Section: Resultsmentioning
confidence: 99%